Perceived health competence and health education experience predict health promotion behaviors among rural older adults: A cross-sectional study - Xia Xie; Jiao Du; Jie He; Youchi Liu; Zihao Li (BMC, 2022)
Abstract Background Health promotion behaviors are key determinant of health and well-being, and also play an important role in promoting successful aging. This study investigated levels of engagement in health promotion behaviors among Chinese rural older adults, and explored effects of perceived health competence, health education activities experience and sociodemographic variables on health promotion behavior in this population. Methods A multicenter cross-sectional survey was performed. Participants were recruited by a multistage, stratified, cluster-sampling procedure from Nanbu County, Sichuan Province, China. All participants completed four paper questionnaires: sociodemographic characteristics and health care status survey, the Chinese version of the health promoting lifestyle profile-II (HPLP-II), perceived health competence scale and Lubben social network scale. Data were collected from July to August 2021. Stepwise multiple linear regression analysis was performed to analyze the effects of different factors on health promotion behaviors. Results A total of 425 rural older adults with an average age of 72.7 years were included in analysis. The overall average score of HPLP-II was 101.6. The stepwise multiple linear regression analysis results showed that those who had higher perceived health competence (β = 0.66, P < 0.001), experienced health education activities (β = 0.254, P < 0.001), had physical examination (β = 0.107, P < 0.001), was married (β = 0.189, P < 0.001), had primary school education or above (β = 0.189, P < 0.001), and had a per capita monthly household income of more than 1000¥ (β = 0.085, P = 0.007), have higher levels of engagement in health promotion behaviors; while the level of health promotion behaviors of the older adults living alone was lower than that of living with their spouse or others (β = -0.192, P < 0.001). Combination of the above variables accounted for a total of 69.1% of the variance in health promotion behaviors. Conclusions: The level of health promotion behaviors among Chinese rural older adults is low. Perceived health competence and health education activities experience are two strong determinants of health promotion behaviors. Comprehensive health promotion programs aimed at improving perceived health competences and health literacy through health education activities may be an important part of optimizing the level of health promotion behaviors among rural older adults.